if f is one to one find an equation for its inverse f(x)= 6/x-3 and f(x) = sqr(x+1) x > -1

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

if f is one to one find an equation for its inverse f(x)= 6/x-3 and f(x) = sqr(x+1) x > -1

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

the first f(x)=6/(x-3) or 6/x-3?
first is f(x) = 6/(x-3)
ok so do you know how you would solve for x?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

solve for x, why do we need to solve for x, should we put (x-3)=0 ?
no to find inverse all you have to do is solve for x and when you get done doing this replace x with f^{-1}(x) and replace f(x)=y with x ok y=6/(x-3) multiply both sides by x-3 y(x-3)=6 yx-3y=6 yx=6+3y x=(6+3y)/y f^{-1})(x)=(6+3x)/x
2nd second one we have y=sqrt(x+1) square both sides y^2=x+1 subtract 1 y^2-1=x x=y^2-1 f^{-1}(x)=x^2-1
thank you very much, really appreciate that

Not the answer you are looking for?

Search for more explanations.

Ask your own question